La sociedad de la información: Génesis, iniciativas, concepto y su relación con las TIC (2012)
This paper presents a literature review about the beginning of  syntagma called Information Society – IS  in academic literature and official documents, how this kind of society has been conceptualizing,  its relationship to the Information and Communication Technology - ICT, and its potential impact on developing countries. For this study were analyzed 44 academic and scientific documents and 44 documents published by international organizations and governments from several countries. This work constitutes an important reference for professionals in Systems Engineering and IT because it describes the general framework of what is expected to achieve in the context of the Information Society, especially in ICT development, which enables the identification of opportunities for action and future research. The main contribution of this work is the synthesis about origin, initiatives and concepts of IS, and its relationship with ICT.  Also, it provides arguments of how the incorporation of ICT can generate impacts on developing countries. Finally we present the efforts made by the government of Colombia to promote the IS as a development model. It is important to say that the discussion about this subject is open, and it is necessary to approach it from different points of view.